2010
DOI: 10.1289/ehp.0901819
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol AF Is a Full Agonist for the Estrogen Receptor ERα but a Highly Specific Antagonist for ERβ

Abstract: BackgroundBisphenol AF has been acknowledged to be useful for the production of CF3-containing polymers with improved chemical, thermal, and mechanical properties. Because of the lack of adequate toxicity data, bisphenol AF has been nominated for comprehensive toxicological characterization.ObjectivesWe aimed to determine the relative preference of bisphenol AF for the human nuclear estrogenic receptors ERα and ERβ and the bisphenol A–specific estrogen-related receptor ERRγ, and to clarify structural character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
125
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(139 citation statements)
references
References 35 publications
(46 reference statements)
13
125
1
Order By: Relevance
“…Although bisphenols including BPAF have been shown to function as activators of ERα under E2-depleted/low conditions, such as in HeLa cells (human cervical adenocarcinoma; negative for aromatase, an enzyme responsible for E2 production), 3,24) this phenomenon was not observed in other cell lines including HepG2 (human hepatocellular carcinoma; positive for aromatase) and Ishikawa (human endometrial adenocarcinoma; positive for aromatase). 4,25) We utilized MCF-7 cells, which produce E2 at pmol levels (i.e., 0.26 pM/10 6 cells), 26) and in the presence of exogenously added 1 nM E2, as expected, the stimulation of ERα by bisphenols was not detected in MCF-7 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bisphenols including BPAF have been shown to function as activators of ERα under E2-depleted/low conditions, such as in HeLa cells (human cervical adenocarcinoma; negative for aromatase, an enzyme responsible for E2 production), 3,24) this phenomenon was not observed in other cell lines including HepG2 (human hepatocellular carcinoma; positive for aromatase) and Ishikawa (human endometrial adenocarcinoma; positive for aromatase). 4,25) We utilized MCF-7 cells, which produce E2 at pmol levels (i.e., 0.26 pM/10 6 cells), 26) and in the presence of exogenously added 1 nM E2, as expected, the stimulation of ERα by bisphenols was not detected in MCF-7 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2) Bisphenols (BPA, BPB, BPS, and BPAF) have been shown to exert positive effects on estrogen receptor (ER)α-mediated transcriptional activation in in vitro studies (i.e., nanomolar concentrations) [3][4][5][6][7] ; however, it currently remains unclear whether these bisphenols affect the expression of ERα/β, and if this is coupled with the "modulation" of estrogen signaling. Therefore, more detailed toxicological data need to be acquired in order to establish the toxicological basis of bisphenols in vitro.…”
mentioning
confidence: 99%
“…Most measured concentrations in the environment are below levels associated with adverse effects on aquatic organisms. However, it has been reported that BPA could cause various ''low-dose effects'', such as decreasing daily sperm production and fertility in male mice (Gupta 2000;Matsushima et al, 2010). And some occasionally environmental levels of BPA exceed the lowest effect concentrations in aquatic organisms and thus could potentially cause some adverse effects on aquatic ecosystems (Crain et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics of BPA have been attributed to the effects on steroid hormone receptors such as ER (Matsushima et al, 2010). Okada et al (2008) reported that BPAF bound more strongly to ERa than BPA, and that it could cause adverse reproductive and developmental effects in several different in vivo and in vitro models (Akahori et al, 2008;Bermudez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation